(untitled) (Biological Sciences - PJSIR, 2000)
Twenty four seed-borne fungibelonging to different genera, weredetected using blotter paper method, from 145seed samples of major legume crops in Pakistan. Of these fungi,Alternaria alternata, Ascochyta spp., Colletotrichum spp., Fusarium spp. andMacrophomina phaseolina were themost frequentandknown as common pathogenic fungi in these crops. Highestnumberofvarious typesof mycoflorawasdetectedinsoybean(14),chickpea (13) followedbymungbean, peaand lentilseeds.Rangeofseedinfectionpercentagevaried inindividualsamplesandcrops. Seven fungi,Aspergillus, Chaetomium, Cladosporium, Mucor, Penicillium, Trichoderma spp.generallynotconsidered field fungiinlegumecrops andareknowntobe involvedindeteriorationof seedsandproductionofmycotoxins, werealsoobserved.It isneededthat thetestlegumecrop seedsmay be tested fortheir healthstatus beforesowingand storageso as toproduce healthycrops.